TATA KELOLA KEBIJAKAN DI SEKTOR PARIWISATA PADA MASA AWAL PANDEMI COVID-19: PENGALAMAN DARI KABUPATEN GUNUNGKIDUL - Aji, Khusnul Bayu; Anandito, Erlangga (Jurnal Pariwisata Tawangmangu, 2023)
Similar to other territories across the globe, the tourism industry in Gunungkidul has also been negatively affected by the COVID-19 pandemic. In response to this dreadful situation, the local government immediately developed various tourism policies. Therefore, this research intends to: a) identify policies issued by the Gunungkidul local government in response to the COVID-19 outbreak crisis; b) analyze the dynamics of the implementation of these policies; and c) examine the appropriation of the policies in accordance with a strategic and holistic framework of disaster and crisis management in tourism. This was a qualitative study in which data were collected through direct observation and literature review. The data in this study were then analyzed using thematic analysis techniques. The findings indicate that local governments published at least five strategic policies during the early period of the COVID-19 pandemic. These policies typically focus on the adaptive capacity dimension, particularly in the domain of strategic implementation, and result in more emergency response measures that are also oriented toward short-term action. It means that, so far, no policy has led to the restoration and reinvestment of the tourism sector in Gunungkidul in an effort to recover from long-term conditions. On the other hand, all stakeholders should go further to initiate policies that point to preventive and mitigating measures that emerge from the current crisis as well as to anticipate similar conditions that may occur in the future.